The C9orf72-SMCR8-WDR41 complex is a GAP for small GTPases. Issue 8 (2nd August 2020) - Tang, Dan; Sheng, Jingwen; Xu, Liangting; Yan, Chuangye; Qi, Shiqian
ABSTRACT: Massive expansions of the hexanucleotide in C9orf72 are the primary genetic origins of familial amyotrophic lateral sclerosis (ALS) and frontal temporal dementia (FTD). Current studies have found that this repeat sequence participates in the disease process by producing neurotoxic substances and reducing the level of C9orf72 protein; however, the progress in the functional study of C9orf72 is slow. Recently, a stable complex, consisting of C9orf72, SMCR8, and WDR41, has been implicated in regulating membrane trafficking and macroautophagy. We reported the cryo-electron microscopy (cryo-EM) structure of the C9orf72-SMCR8-WDR41 complex (CSW complex), unveiling that the CSW complex is a dimer of heterotrimers. Intriguingly, in the heterotrimer of the C9orf72-SMCR8-WDR41, C9orf72 interacts with SMCR8 in a manner similar to the FLCN-FNIP2 complex. Nevertheless, WDR41 is connected to the DENN domain of SMCR8 through its N-terminal β-strand and C-terminal helix but does not directly interact with C9orf72. Notably, the C9orf72-SMCR8 complex was demonstrated to act as a GAP for RAB8A and RAB11A in vitro .